Mechanics of materials - Beer, Ferdinand P.; Johnston, E. Russell; DeWolf, John T.; Mazurek, David F. (McGraw-Hill, 2012)
Illustrates numerous engineering examples that students both understand and relate to in theory and application. This title includes coverage ranging from the detailed examples, to the homework problems, to the carefully developed solutions manual.